Employees' perceptions of barriers to participation in training and development in small engineering businesses. Issue 7 (14th September 2015) - Susomrith, Pattanee; Coetzer, Alan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to investigate barriers to employee participation in voluntary formal training and development opportunities from the perspective of employees in small engineering businesses. Design/methodology/approach – An exploratory qualitative methodology involving data collection via site visits and in-depth semi-structured interviews with 20 employees in five small engineering businesses was used. Interviews explored the role of developmental proactivity and employees' perceptions of conditions in the immediate work environment and industry sector that represent barriers to their participation in formal training and development. Interview transcripts were analysed using thematic analysis. Findings – Three key findings are as follows. First, proactive behaviour regarding access to external training and development is muted in small business settings because of strong resource allocation norms. Second, factors in the internal work environment rather than the industry sector constitute the major barriers to training and development. Third, owner-managers and employees appear to have significantly differing perspectives of barriers to training and development. Research limitations/implications – The findings suggest avenues for future research. These include examining how workplace norms influence employee behaviour with regard to accessing formal training and development and investigating the learning strategies that employees use to compensate for a lack of access to training and development. Originality/value – Research into relatively low levels of employee participation in formal training and development in small businesses is deficient because it predominantly involves surveys of owner-managers' opinions. This study is novel because it seeks to generate new insights not previously articulated by employees. The study yielded four propositions that have practical and research implications.